Analisis Kinerja Ombudsman Republik Indonesia Perwakilan Jawa Tengah Dalam Rangka Penanganan Laporan Masyarakat - Dyah Hariani; Tri Yanti Nur Irson Sitorus (Jurnal Ilmu Administrasi Negara ASIAN (Asosiasi Ilmuwan Administrasi Negara), 2019)
Maladministration is an inapropriate behavior which is not compatible with the principle of a good public service. Citizens often unsatisfied with the service they received. Number of public service executors do not give the procedural sevice, take too much time, do the illegal extraction, and there are numbers of aladministration happened in public service execution. Indonesian Republic’s Ombudsman is a vice Ombudsman in Middle Java fuctioned to monitor and prohibit maladministration in Middle Java. In monitoring, Ombudsman takes action in finishing the report from the citizens through clarification, investigation, and create a conclusion and decision in form of recomendation and suggestion. The aim of this research is to analyze the work and the factors involves Indonesian Ombudsman’s work in Middle Java in handling the report. The theory used in this research is work by considering the Productivity, Service Quality, Responcivity, Responsibility, and Accountability. This research used Qualitative research method with Descriptive data processing. The data was collected by using interview, observation, and documentation. By using core informant as the main sourse and triangulation technique as the source of valid data. After the research, the Indonesian Republic’s Ombudsman in Middle Java is ategorized to good. But it can’t be said as an optimal one because there are some obstacles in finishing the report for human resources, material, facility, and the agency, and the citizens’ undertstanding about Ombudsman right is still bad.